ناول "تنہا" از سلمی اعوان ، المیہ مشرقی پاکستان کے تناظر میں(تجزیاتی مطالعہ) (Al-Aasar, 2025)
The dissolution of Pakistan in 1971, which resulted in the secession of its eastern wing as Bangladesh, is the most tragic event in the nation's history. Although international political dynamics played their part, the primary drivers of this separation were internal: profound cultural and linguistic disparities, systemic political marginalization of East Pakistan by the central government (based in the West), and economic neglect.Salma Awan's novel Tanha tells the story of a young woman who travels from West Pakistan to East Pakistan for her education. This narrative device provides a personal perspective on the escalating crisis.Through this student's experiences, Salma Awan documents the real-world conditions of the time—the rising cultural tensions, the increasing military presence, and the volatile political environment preceding the civil war. The novel does not merely glorify the independence movement; it presents a complex picture. It acknowledges the legitimate grievances and sacrifices of the Bengali activists while also portraying the confusion, fear, and conflicting loyalties experienced by many, including those from West Pakistan who were present as the situation deteriorated. Thus, Tanha presents a nuanced and realistic narrative of a nation tearing itself apart